Perceived Effects of Fallouts of the 2023 General Elections on Orientation of Tertiary Education Students in Imo State - Nnajieto, Charles Chibuzor; Iwejuo, Christogonus Amara (International Journal of Humanities, Education, and Social Sciences, 2024)
This study investigates the perceived effects of the 2023 general elections on the orientation of undergraduate students in Imo State, Nigeria. Given the fundamental role of credible, free, and fair elections in a democracy, this research aims to gauge the opinions of young Nigerians, particularly those in higher education institutions, who are presumed to be more enlightened and actively involved in their Student Union Governments. Adopting a public opinion survey design, the study utilized a stratified sampling technique to distribute questionnaires among the respondents. The collected data, representing public opinion polls, were analyzed to discern prevailing sentiments. Results indicate a significant disillusionment among undergraduates, with many expressing a loss of confidence and interest in Nigeria's electoral system. The study reveals that the majority of students believe that the Independent National Electoral Commission (INEC) has failed the citizens, particularly in light of the high expectations set by the introduction of the Bimodal Voter Accreditation System (BVAS), which promised transparency but ultimately did not fulfill its potential. This disillusionment has led to a widespread desire among young Nigerians to emigrate in search of better governance. The study recommends that electoral bodies prioritize restoring the integrity of democratic institutions by ensuring the conduct of credible elections in Nigeria.